Factors associated with health information systems that influence continuity of TB care between a District hospital and Primary Healthcare facilities - Esack, Tasneem (Department of Public Health and Family Medicine, 2025)
Background: South Africa is well known to have a high burden of Tuberculosis (TB) disease. The Western Cape has been identified as having one of the highest numbers of new infections of TB per year in South Africa. TB is the cause of significant mortality and morbidity and has substantial financial implications for patients and the health system. As a result of high levels of HIV, poverty and overcrowding TB has been difficult to eradicate. The significant burden of disease, the caseloads and staff shortages also contribute to challenges to successfully continuing care of TB patients. It has been noted that as much as 24% of TB patients may be lost to follow up (LTFU) in certain districts of the Western Cape. While previous studies have looked at factors that influence LTFU and continuity of care (COC), no studies have examined how the design and use of Health Information Systems (HIS) may influence these outcomes. This study aims to describe the current use of HIS in the discharge process of a TB patient at a district hospital in Western Cape and further aims to identify how HIS may facilitate or create barriers to successfully continuing a patient's TB treatment at primary healthcare level after discharge from a district hospital. Methods: The study was conducted through two phases. Phase 1, secondary data analysis of process maps previously created to understand the TB care pathways and the associated gaps in care within a district hospital and phase 2, a semi-structured interview process. Analysis of both phases involved qualitative thematic analysis attempting to identify and unpack Health Information Systems (HIS) challenges associated with TB care. Results: Barriers were identified which prevented seamless use of HIS and which did not promote COC. These included poor understanding of TB administrative and referral processes, and what is required to successfully link to TB care and continue care at primary healthcare (PHC) facilities. Further barriers were resources and usability of the HIS, as well as data integrity and fragmented HISs. The only facilitators identified was the availability of clinical information where access was possible and data was complete, as well as an electronic referral platform to TB hospitals. Conclusion: Obstacles exist to the effective utilization of HISs in ensuring continuity of TB care between district hospitals and community clinics. To mitigate some of these limitations, we propose that training on SOPs, HISs, and administrative procedures for TB management be intensified. Clarifying ambiguities regarding data, workflows, and HIS prerequisites that support COC could help HCWs better facilitate COC through HIS usage. Additionally, organizations should strive to minimize resource deficiencies hindering HIS utilization. Insights from the TB hospital referral system can be leveraged to enhance care linkage.